The synthesized factors related to flood preparedness literacy and behaviors among older adult in community - Boonyaratkalin, Panisa; Chompoonud, Somjinda; Khumpheephant, Sirimol (Thai Journal of Nursing, 2022)
This documentary research aimed to synthesize factors related to flood preparedness literacy and behaviors among older adult in community. The document of thirty literatures published during May 2011 to May 2021 from online databases, were selected. Content analysis was used in data analysis. The results revealed that there were 3 key factors related to flood preparedness literacy and behaviors among older adult in community; 1) internal factors including demographic factor (age, education level, and family income), health perception factors (visual and hearing ability, advanced self-help ability, and health status), and feeling factors (self-efficacy and flood preparedness attitude), 2) external factors including social support, media and source of information, and 3) situation factors including flood experience and living in flood risk area.